Konsep Pendidikan Tauhid dalam Perspektif Al-Ghazali, Ibn Sina dan Al-Farabi: Kajian Komparatif - Hufron, Hufron; Jamaluddin, Muhammad; Muthohar, Ahmad (CV. Satria Jaya, 2025)
This study aims to examine the concept of tawhid-based education in the thought of three classical Islamic scholars: Imam Al-Ghazali, Ibn Sina, and Al-Farabi. This qualitative research employs a literature review approach focusing on the primary works of these scholars. The findings reveal that despite their different scientific and methodological orientations—namely spiritual-sufistic (Al-Ghazali), rational-philosophical (Ibn Sina), and ethical-political (Al-Farabi)-all three regard tawhid (the oneness of God) as the core foundation of education. Al-Ghazali emphasizes spiritual purification and moral formation; Ibn Sina positions tawhid as the ultimate outcome of intellectual and philosophical inquiry; and Al-Farabi integrates tawhid into the ideal construction of a virtuous and rational society. The novelty of this research lies in its comparative analysis of the three thinkers from the perspective of tawhid-based education, which remains underexplored in contemporary Islamic educational studies. This study recommends the integration of these diverse approaches into modern Islamic curricula to develop holistic individuals-intellectually competent, morally upright, and rooted in tawhid.